Current trends in studying glaucoma: a review of published data - L.A. Zaporozhetc; V.N. Alekseev; E.A. Egorov; Е.В. Martynova; Yu.A. Alekseev (РМЖ "Клиническая офтальмология")
L.A. Zaporozhetc1, V.N. Alekseev2, Е.А. Egorov3, Е.В. Martynova2, Yu.A. Alekseev2 1Leningrad Regional Clinical Hospital, St.-Petersburg, Russian Federation 2I.I. Mechnikov North-Western State Medical University, St.-Petersburg, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to analyze recently published data on the trends in glaucoma studies, etiology, pathogenesis, clinical course, diagnostic challenges, and treatment for glaucoma based on current recommendations and published data over the last 50 years. Materials and Methods: this paper reviews English published data on glaucoma indexed in PubMed database and papers from the "Ophthalmological Journal" and "American Journal of Ophthalmology over 50 years (1970–2019), and open access journals («National Journal Glaucoma" and "British Journal of Ophthalmology") over the last ten years (2010–2019). Results: published data analysis demonstrated a steadily increased interest in studying all aspects of glaucoma from 1970 until now. In 2010–2019, there was a growing interest in the personalized approach to the study and treatment of glaucoma. Over this period, studies on the fundamental basis of glaucoma and its surgical management became the priority in Russia and foreign  countries. Meanwhile, the interest in glaucoma surgery is still predominant in Russian published data from 1970 until now (although its growth rate reduced by 2019). In the 1980s, studying the functional status of glaucoma using automated perimetry gained the most popularity. Since 2000, the interest has switched to the morphometry of optic nerve head (ONH) using optical coherence tomography. Conclusions: primary studies on glaucoma are similar in Russia and foreign countries, i.e., theoretical aspects (etiology and pathogenesis) and improving surgical techniques. Our findings demonstrate a growing interest in a personalized approach to study glaucoma. Since 2010, there has been an increase in domestic published data on conservative treatment for glaucoma. To date, the most promising diagnostic modality is ONH morphometry. Keywords: primary glaucoma, published data, automated perimetry, Heidelberg retinal tomography, optical coherence tomography, glaucoma treatment. For citation: Zaporozhetc L.A., Alekseev V.N., Egorov Е.А. et al. Current trends in studying glaucoma: a review of published data. Russian Journal of Clinical Ophthalmology. 2021;21(4):194–199 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-194-199.